HOW “DIGITAL” IS THE NEW SERBIAN LAW ON DIGITAL ASSETS? - Motika, Zeljka (Pravni zapisi, 2022)
Papers focuses on the legislative changes from 2021 that the Law on Digital Assets introduced into the legal system of the Republic of Serbia and contextualizes the amendments from the perspective of existing practice. Introductory part evaluates the issue of whether blockchain technology can secure trust and safety in the transactions that are executed via Internet by parties from all over the world, as well as reasons that created the regulatory framework for values that are transferred over distributed ledger technologies infrastructures. Main part of the paper examines in detail the legislative solutions within the Law on Digital Assets as well as key exceptions and terms and their impact on the local economy. The section is followed by an overview of the draft legislation in EU in the field as well as how it may impact Serbian economy as a third country. Aside from concluding remarks on legislative changes domestically, the paper outlines potential upcoming challenges related to blockchain and instruments that may require a different approach in regulation.